If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(2t + 9) = -42 Reorder the terms: -6(9 + 2t) = -42 (9 * -6 + 2t * -6) = -42 (-54 + -12t) = -42 Solving -54 + -12t = -42 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + -12t = -42 + 54 Combine like terms: -54 + 54 = 0 0 + -12t = -42 + 54 -12t = -42 + 54 Combine like terms: -42 + 54 = 12 -12t = 12 Divide each side by '-12'. t = -1 Simplifying t = -1
| 6p-4p=3p-4 | | A/25 | | 2x=6+26 | | 3y-5*4=2y+1 | | 4y+16x=-28 | | 5(f-3)=20 | | (X-3)/4=1/2 | | (9*x)+(5*y)=28 | | 3.4+0.2d=1.4 | | 2mx+(m-2)y-2=0 | | 3.4+02d=1.4 | | 2a-7=6 | | 125/x=15 | | 4/9d=-2/9 | | (x-18)*6=48 | | tan=x | | 7/4*3/2 | | 0.5(4x+18)=-1.5(5x)-2(3x+4.5) | | t-34=61/4 | | 4x-12=3x+7 | | -32-28x=-10-6x | | x-3x^1/2=4 | | 4+3t-5t=16 | | 3x-10=20x+3 | | f(x)=ln(x^8)-lnx | | (u-3)*8=56 | | 4=m/2.5 | | x-20=30x-20 | | (q-8)*4=12 | | 17x+3=-10 | | (3x)/5=(21-7y)/10 | | 5n-2=387 |